Limbus Vertebra in the Thoracic Spine: A Case Report - Sarfinaz Ataoğlu; Rumeysa Samanci (Düzce Tıp Fakültesi Dergisi)
The limbus vertebra, first described by Christian Schmorl in 1927, is considered a variant of a normal vertebra in the literature. It is a triangular fragment of bone that separates from the anterosuperior corner of the vertebra and is usually discovered incidentally via X-ray. Typically, it is asymptomatic due to its location. A limbus vertebra can be mistaken for a fracture, discitis, Schmorl's node, or tumor, which may lead to unnecessary surgical intervention. Therefore, it should be included in the differential diagnosis, especially in patients with a history of trauma, when their clinical condition is assessed. Limbus vertebrae most commonly affect the lumbar spine and, less frequently, other regions of the vertebral column. In this case report, an incidental finding of a limbus vertebra in the thoracic spine in a 30-year-old female patient was presented.